PENERAPAN PEMBELAJARAN BERBAHAN LOOSE PART IN DOOR UNTUK MEMBANGUN MERDEKA BELAJAR ANAK USIA DINI - Sumarseh Sumarseh; Delfi Eliza (Generasi Emas: Jurnal Pendidikan Islam Anak Usia Dini, 2022)
The background of this research is the child’s lack of independence in developing the desired abilities. This situation can be seen when the child conveys the sentence “can’t mother” or “like which mother” to complete a play activity thet can produce a free work. This is because children’s play activities still use children’s worksheets (LKA), not according to the child’s wishes or interests. The pupose of this research is to describe descriptively qualtatively about learning by applying loosepart learning media to build independent learning for early childhood with the number of research subjects 2 children, namely 5 boys and 7 girls.